Global magnitude and temporal trend of mesothelioma burden along with the contribution of occupational asbestos exposure in 204 countries and territories from 1990 to 2019: Results from the Global Burden of Disease Study 2019. (November 2022) - Han, Yali; Zhang, Tongchao; Chen, Hui; Yang, Xiaorong
Abstract: Understanding the burden of mesothelioma with the contribution of occupational asbestos exposure globally provides essential foundations for cancer control, policy decisions and resource allocation. Globally, 34, 511 incident cases, 29, 251 deaths and 668, 104 disability-adjusted life years (DALYs) of mesothelioma were estimated in 2019. The age-standardized rates of incidence, mortality and DALYs all showed a slightly declining trend over the past 30 years, but the latest absolute number of mesothelioma burden almost doubled since 1990. The burden rate decreased among the population aged under 70 years, but increased among the population aged over 80 years, especially in the High socio-demographic index (SDI) region. The burden rate of mesothelioma attributable to asbestos exposure was positively associated with SDI at the national level. This study depicted a continuous increase in mesothelioma burden globally over the past 30 years. Controlling occupational asbestos exposure will reduce the mesothelioma burden, especially for higher SDI regions. Graphical Abstract: ga1 Highlights: This study summarized the latest global spatiotemporal patterns of mesothelioma burden. Globally, 34, 511 incident cases and 29, 251 deaths of mesothelioma were estimated in 2019, doubling since 1990. The male-to-female ratio in age-standardized burden was 3 and further widened. Age-specific burden rate dropped under 70 years, but rose over 80 years, especially in the developed regions. The mesothelioma attributable to occupational asbestos exposure was positively associated with socio-demographic index.